Preliminary Evaluation of Tick Protein Extracts and Recombinant Ferritin 2 as Anti-tick Vaccines Targeting Ixodes ricinus in Cattle - Knorr, Sarah; Anguita, Juan; Cortazar, Julen T.; Hajdusek, Ondrej; Kopáček, Petr; Trentelman, Jos J.; Kershaw, Olivia; Hovius, Joppe W.; Nijhof, Ard M. (Frontiers in Physiology, 2018)
Anti-tick vaccines have the potential to be an environmentally friendly and cost-effective option for tick control. In vaccine development, the identification of efficacious antigens forms the major bottleneck. In this study, the efficacy of immunization with recombinant ferritin 2 and native tick protein extracts against Ixodes ricinus infestations in calves was assessed in two immunization experiments. In the first experiment, each calf (n=3) was immunized twice with recombinant ferritin 2 from I. ricinus (IrFER2), tick protein extract (TPE) consisting of soluble proteins from the internal organs of partially fed I. ricinus females, or adjuvant, respectively. In the second experiment, each calf (n=4) was immunized with protein extracts from the midgut (ME) of partially fed females, the salivary glands (SGE) of partially fed females, a combination of ME and SGE, or adjuvant, respectively. Two weeks after the booster immunization, calves were challenged with 100 females and 200 nymphs. Blood was collected from the calves before the first and after the second immunization and fed to I. ricinus females and nymphs using an in vitro artificial tick feeding system. The two calves vaccinated with whole TPE and midgut extract (ME) showed hyperemia on tick bite sites two days post tick infestation and exudative blisters were observed in the ME-vaccinated animal, signs that were suggestive of a delayed type hypersensitivity (DTH) reaction. Significantly fewer ticks successfully fed on the three animals vaccinated with TPE, SGE or ME. Adults fed on the TPE and ME vaccinated animals weighed significantly less. Tick feeding on the IrFER2 vaccinated calf was not impaired. The in vitro feeding of serum or fresh whole blood collected from the vaccinated animals did not significantly affect tick feeding success. Immunization with native I. ricinus tick protein extracts thus conferred a strong immune response in calves and significantly reduced the feeding success of both nymphs and adults. In vitro feeding of serum or blood collected from vaccinated animals to ticks did not affect tick feeding, indicating that antibodies alone were not responsible for the observed vaccine immunity.